Diversity in Gold Finger Structure Elucidated by Traveling‐Wave Ion Mobility Mass Spectrometry. Issue 16 (20th March 2017) - Du, Zhifeng; de Paiva, Raphael E. F.; Nelson, Kristina; Farrell, Nicholas P.
Abstract: Traveling wave ion mobility (TWIM) mass spectrometry (MS) is a powerful method for the structural and conformational analysis of proteins and peptides, enabling the differentiation of isomeric peptides (or proteins) that have the same sequence but are modified at different residues. In this study, the TWIM‐MS technique was used to separate isomeric Au I metallopeptide ions that were formed by Zn II displacement from the parent zinc fingers (ZFs). The synthetic gold finger peptides were derived from the C‐terminus of the HIV nucleocapsid p7 protein (NCp7‐F2) and finger 3 of the Sp1 transcription factor (Sp1‐F3). TWIM‐MS enabled the acquisition of distinct product ion spectra for each isomer, clearly indicating the binding sites for the major conformers in the presence of multiple coordination possibilities. Collision cross‐section measurements showed that the aurated peptide has a slightly more compact structure than the parent zinc compound NCp7‐F2, which showed only one conformation. Abstract : A golden opportunity : Traveling‐wave ion mobility (TWIM) mass spectrometry (MS) was used to separate isomeric metalated peptide ions derived from gold(I) complexes, enabling the acquisition of distinct product ion spectra for each isomer (blue and red). Measurements of the collision cross‐sections showed that the aurated peptide has a slightly more compact structure than the parent zinc finger.